2020
DOI: 10.1093/abbs/gmaa087
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1/miR-140-3p/MAPK1 mediates the viability and survival of coronary endothelial cells and affects coronary atherosclerotic heart disease

Abstract: Studies have shown that long non-coding RNAs (lncRNA) play critical roles in coronary atherosclerotic heart disease (CAD). However, the function of lncRNA nuclear enriched abundant transcript 1 (NEAT1) in CAD is unclear. In this study, we aimed to investigate the functions of lncRNA NEAT1 in CAD. RT-PCR and western blot analysis were carried out to examine the expressions of related RNAs. Colony formation assay, cell proliferation assay, apoptosis assay, and dual-luciferase reporter assay were conducted to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…For example, miR-223-3p could alleviate vascular endothelial injury in kawasaki disease [37]. NEAT1/ miR-140-3p/MAPK1 mediated the viability and survival of coronary endothelial cells and affected coronary atherosclerotic heart disease [38]. MiR-17 regulated the proliferation and apoptosis of endothelial cells in CHD [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-223-3p could alleviate vascular endothelial injury in kawasaki disease [37]. NEAT1/ miR-140-3p/MAPK1 mediated the viability and survival of coronary endothelial cells and affected coronary atherosclerotic heart disease [38]. MiR-17 regulated the proliferation and apoptosis of endothelial cells in CHD [39].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK1 is a protein-coding gene with transferase activity and tyrosine kinase activity that is involved in the transfer of phosphorus-containing groups in signaling pathways. Studies have shown that MAPK1 is upregulated by miR-140-3p and inhibits CAD cell apoptosis (33). Knockout of ABL1 gene inhibits c-Abl activity and significantly reduces apoptosis of VSMCs and synthetic phenotypic transformation induced by Ang II both in vivo and in vitro (34).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al indicated that RELA, a key transcription factor for hypoxic response, can promote the expression of CXCL12 under hypoxic conditions by combining with LINC01693 and thus promote hypoxia-induced angiogenesis [46]. MAPK1, belonging to the MAPK family, can be activated by LncRNA NEAT1 to enhance cell viability and inhibit cell apoptosis [47]. Wei et al illustrated that the methylation of the TP53 promoter may be related to the occurrence of atherosclerosis ,which has got wider audience in the research of atherosclerosis [48].…”
Section: Discussionmentioning
confidence: 99%